The EdD and one bedtime story more! An exploration of the Third-Space inhabited by mothers working in educational leadership whilst studying for a professional doctorate. (October 2017) - Gibson, Poppy; Shanks, Rehana; Dick, Suzie
This article focuses on the ever-present pressures, tensions and opportunities for women leaders in education, and the link between identity, pursuit of excellence and the pursuit of a complete, worthwhile life. It highlights the experience of three women in educational leadership who are undertaking Doctoral studies while balancing the needs of family, work and study. It aims to explore how the multiple facets of a woman's identity come together to enable each to lead in an educational setting. We consider 'the third space in an identity', a place in which 'everything comes together' and we call into question whether a woman's identity as a leader is ever truly fixed. The implications of this narrative are that it may serve to inform and challenge those responsible running a Doctorate in Education (EdD) programme. We highlight the implications of leadership, including capabilities from a gendered perspective and the impact and challenges on us in navigating the twilight zone. We conclude that lifelong learning needs to meet the need of learners.